(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2024)
In this article I discuss the relationship between journalism, event and reality from the analysis of the news production operations that the portal of the Argentine daily La Nación made of the Cocaine Case of Puerta 8, on February 2, 2022, in Buenos Aires. I seek to answer how journalism operates the production of news about the event and what effects of meaning it produces on the sense of reality. Assuming that reality is a social construction (Berger & Luckmann, 1985) and that the event is simultaneously fact and narrative (Quéré, 2005), I adopt four analytical categories: subjects and objects – implicated in the fact in its indicial character; and concept and strategy – which concern the narrative as a production of meaning. It follows that it is in the articulation of these categories in recognition and production operations that journalism participates in a peculiar way in the reiteration and stabilization of a common sense about reality.